Flexible Waterproof Piezoresistive Pressure Sensors with Wide Linear Working Range Based on Conductive Fabrics - Xu, Hongcheng; Gao, Libo; Wang, Yuejiao; Gao, Ke; Hu, Xinkang; Wang, Liang; Mu, Meng; Liu, Min; Zhang, Haiyan; Wang, Weidong; Lu, Yang (Nano-Micro Letters, 2020)
Developing flexible sensors with high working performance holds intense interest for diverse applications in leveraging the Internet-of-things (IoT) infrastructures. For flexible piezoresistive sensors, traditionally most efforts are focused on tailoring the sensing materials to enhance the contact resistance variation for improving the sensitivity and working range, and it, however, remains challenging to simultaneously achieve flexible sensor with a linear working range over a high-pressure region (> 100 kPa) and keep a reliable sensitivity. Herein, we devised a laser-engraved silver-coated fabric as “soft” sensor electrode material to markedly advance the flexible sensor’s linear working range to a level of 800 kPa with a high sensitivity of 6.4 kPa−1 yet a fast response time of only 4 ms as well as long-time durability, which was rarely reported before. The integrated sensor successfully routed the wireless signal of pulse rate to the portable smartphone, further demonstrating its potential as a reliable electronic. Along with the rationally building the electrode instead of merely focusing on sensing materials capable of significantly improving the sensor’s performance, we expect that this design concept and sensor system could potentially pave the way for developing more advanced wearable electronics in the future. Highlights: 1 The laser-engraved method was introduced to fabricate the electrode for the sensor. 2 The sensor showed a wide linear working range, superior sensitivity, and fast response time and also exhibited excellent viability in a wet situation. 3 Wireless integrated network sensors successfully monitored the health states.